FRAKSINASI DAN BIOAVAILABILITAS LOGAM Pb DAN Cr DALAM SEDIMEN DI PELABUHAN BENOA - Ni Luh Eka Lusiana Dewi; Emmy Sahara; A. A. I. A Mayun Laksmiwati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
The fractionation and the bioavailability determination of Pb and Cr in sediment of Benoa Bay have been studied. This study was aimed to determine the metals concentration in their various chemical forms. A 63 µm nylon mesh screen was used for wet and dry sieving the sediment samples. Through fractionation, the bioavailabilities of both metals could be determined. For the total metals determinations, the samples were digested with aqua regia which is the mixture of HCl and HNO3(3:1). Fractionation was done with the application of the four steps sequential extraction technique. All metals measurements were carried out with the use of the technique of Atomic Absorption Spectrophotometry. The total concentrations of Pb in sediments sieved in wet and dry conditions were 18.4852 mg/kg and 23.3974 mg/kg, respectively, whereas the total concentrations of Cr in those of wet and dry conditions were 17.7131 mg/kg and 24.9371 mg/kg, respectively. The fractionations of Pb in sediments sieved in wet and dry conditions showed the same paterns which were as follow: freely, leachable, dan exchangeable (EFLE) fraction < Fe/Mn-oxide fraction < resistant fraction < organic dan sulfide fraction. The fractionation of Cr in wet sieved sediment was as follows: EFLE fraction < resistant fraction < organic and sulfide fraction < Fe/Mn-oxide fraction whereas that of Cr in dry sieved sediment was as follows EFLE< Fe – Mn oxide fraction < resistant fraction < organic and sulfide fraction. The bioavailable and resistant fractions found for Pb in wet sieved sediment were 74.13% and 22.88%, respectively, whereas those of Pb found in dry sieved sediment were 82.84% dan 13.85%, respectively. The bioavailable and resistant fractions found for Cr in wet sieved sediment were 77.59% and 11.23%, respectively, whereas those of Cr in dry sieved sediment were 90.55% and13.21%, respectively.